2019
DOI: 10.1007/s40265-019-01195-w
|View full text |Cite|
|
Sign up to set email alerts
|

Trifluridine/Tipiracil: A Review in Metastatic Gastric Cancer

Abstract: Trifluridine/tipiracil (Lonsurf®) is a fixed-dose combination tablet comprising trifluridine, an antineoplastic nucleoside analogue, and tipiracil, a thymidine phosphorylase inhibitor. Trifluridine/tipiracil has recently been granted an additional indication in the USA for the treatment of metastatic gastric cancer, including gastroesophageal junction adenocarcinoma, in patients who have been previously treated with at least two systemic treatment regimens, and has received a positive opinion for this indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Some of the frequently used drugs in antiviral therapy and translocated by ENT2 (and another NTs) are zidovudine, zalcitabine, didanosine, and rivabirine [45]. The nucleoside derivatives commonly used in cancer treatment such as cytarabine [55], gemcitabine [55], fludarabine [50], cladribine [5], clofarabine [5], trifluridine [56], 5fluorouracil [57], and 50-deoxy-5-fluorouridine (5 ′ dFUR) [58] are translocated by a variety of NTs including ENT2 [4,37]. For example, gemcitabine has activity in various solid tumors and some hematological malignant diseases [54].…”
Section: Physiological Roles Of Ent2mentioning
confidence: 99%
“…Some of the frequently used drugs in antiviral therapy and translocated by ENT2 (and another NTs) are zidovudine, zalcitabine, didanosine, and rivabirine [45]. The nucleoside derivatives commonly used in cancer treatment such as cytarabine [55], gemcitabine [55], fludarabine [50], cladribine [5], clofarabine [5], trifluridine [56], 5fluorouracil [57], and 50-deoxy-5-fluorouridine (5 ′ dFUR) [58] are translocated by a variety of NTs including ENT2 [4,37]. For example, gemcitabine has activity in various solid tumors and some hematological malignant diseases [54].…”
Section: Physiological Roles Of Ent2mentioning
confidence: 99%
“…[ 19 ] However, resistance to chemotherapeutic agents often leads to treatment failure, [ 20 ] once resistance appears, treatment programs will become limited. [ 21 ] Therefore, more optimized chemotherapy agents and therapy methods will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that trifluridine/tipiracil has a positive efficacy on patients with advanced GC and its toxicity is acceptable, [ 10 ] moreover, trifluridine/tipiracil monotherapy was beneficial to the median PFS and OS values of patients with advanced GC, [ 10 , 19 , 21 ] and it has well tolerance. [ 18 ] Trifluridine has 2 antitumor mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibits de novo purine synthesis Produces genotoxic thioguanine nucleotides that inhibit DNA and RNA synthesis and alter their subsequent metabolism [7,9] Thymidine phophorylase inhibitor Tipiracil Hydrochloride (TAS-102) Induces cell cycle arrest at G2 phase and DNA double-strand breaks with enhanced drug potency. [135,136] Antifolate Methotrexate, Pemetrexed…”
Section: Discussionmentioning
confidence: 99%